(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-70-82 The aim of this article is to identify the features of speech behavior of video bloggers from the point of view of pragmalinguistics, where the main object of the research is the communicant’s conscious and unconscious choice of speech means. The method of traditional content analysis is used to study the conscious choice of language means by a video blogger, while the method of modified content analysis is used to study the unconscious choice. Fragments of speech of videoblogers, whose videos are devoted to retro vehicles reviews were taken as a research material. This article defines such concepts as Internet discourse, blog and video blog, and also identifies and shows on examples the common linguistic features that are found among video bloggers in the field of retro transport. These features will allow to further form speech portraits of video bloggers and determine their personal traits. These traits show what norms of culture, behavior, communication, even the psychology of people’s thinking are formed among representatives of different generations under the influence of the World Wide Web. Key words: Internet discourse, blog, video blog, video blogger, speech behavior, speech portrait, lexical features, grammatical features, syntactic language features